MO046: Exome sequencing of Israeli Druze individuals on dialysis reveals common as well as population- specific monogenic etiologies in ∼30%. (3rd May 2022) - Shlomovitz, Omer; Yagel, Dina; Barel, Ortal; Atias-Varon, Danit; Eliyahu, Aviva; Bathish, Younes; Frajewicki, Victor; Kushnir, Daniel; Zaid, Rinat; Assady, Suheir; Tchirkov, Marina; Hassan, Kamal; et al.
Abstract: BACKGROUND AND AIMS: Genetic etiologies are estimated to affect ∼10% of adults with advanced CKD. However, significant population disparities in genetic kidney disease exist and population-based screening are lacking especially among minority groups. The Druze population is a middle-eastern minority with high rates of end-stage renal disease (ESRD) and consanguinity, which suggests high rates of population-specific monogenic CKD etiologies. We therefore hypothesized that by exome sequencing we will identify a unique distribution of monogenic ESRD causes as compared with prior studies and that important ramifications for clinical practice may ensue. METHOD: We initiated a national multicenter study of all Israeli dialysis units in order to provide comprehensive evidence for ESRD's genetic basis (Israeli ESRD Genetic Consortium Cohort). Specifically, during 2020, we recruited 97% ( n = 94) of Israeli Druze individuals on dialysis from 12 different hospitals and community-based units. We conducted exome sequencing and diagnostic analysis for all patients. We assessed the diagnostic yield of genetic analysis and its relation to baseline clinical phenotypes. RESULTS: Overall, the cohort consists of 94 individuals from 91 different families with first-degree consanguinity rate of 28%. Participants mean age was 62 years (ranging from 18 to 88 years). Most common primary clinical diagnoses were diabetic kidney disease, nephropathy of unknown origin, glomerular or cystic kidney disease, together encompassing 90% of all cases. None had previous molecular diagnosis. Using exome sequencing, we identified a genetic etiology in 27 out of 94 (28.7%) participants. We identified WDR19 (NPHP13) homozygous mutation c.878G > A (p.C293Y) as the most common genetic diagnosis (5.3%). Follow-up clinical characterization revealed that all affected individuals exhibited non-syndromic adulthood-onset ESRD, supporting a profound mutation-dependent phenotypic heterogeneity and weak pre-exome phenotypic specificity. Other prevalent genetic diagnoses included type IV collagen, PKD1, PKD2 and UMOD mutations as well as monogenic forms of diabetes and hyperlipidemia. Molecular diagnosis corresponded to the pre-exome clinical diagnosis in only one-third of the participants. CONCLUSION: Exome sequencing in Druze with ESRD yields a genetic diagnosis in just <30% of cases with WDR19 mutation being the most prevalent single-gene etiology. These results, which remarkably inform clinical management, emphasize the importance of revealing population-specific mutations given the underutilization of genetic testing, particularly among adult minorities.